ANALYSIS OF THE EFFECT OF EXCHANGE RATES ON INDONESIAN EXPORTS PERIOD OF 1982 – 2015 - Izaac Tonny Matitaputty (Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2018)
This study aims to see the development of exports in the country, to know how the exchange rate (exchange rate) and economic growth (GDP) affect the export conducted and to know how much time it will take to get back to the initial balance if the economy experiences shocks.The method used in this research was Cointegration Test and Error Correction Model Engle-Granger. The results showed that there was a long-term relationship (cointegration) between independent variables and dependent variables. Taken together through the F test and the partial test through t test, independent variables significantly affected Indonesian exports.Keywords: Exchange, Export, Growth, Cointegration, Error Correction Models